Pharmacokinetics of intraosseous and central venous drug delivery during cardiopulmonary resuscitation - Hoskins, Stephen L.; do Nascimento, Paulo [UNESP]; Lima, Rodrigo M. [UNESP]; Espana-Tenorio, Jonathan M.; Kramer, George C. (Elsevier B.V., 2012)
We compared the pharmacokinetics of intraosseous (IO) drug delivery via tibia or sternum, with central venous (CV) drug delivery during cardiopulmonary resuscitation (CPR).Methods: CPR of anesthetized KCl arrest swine was initiated 8 min post arrest. Evans blue and indocyanine green, each were simultaneously injected as a bolus with adrenaline through IO sternal and tibial needles, respectively, n = 7. In second group (n = 6) simultaneous IO sternal and IV central venous (CV) injections were made.Results: Peak arterial blood concentrations were achieved faster for sternal IO vs. tibial IO administration (53 +/- 11 s vs. 107 +/- 27 s, p = 0.03). Tibial IO dose delivered was 65% of sternal administration (p = 0.003). Time to peak blood concentration was similar for sternal IO and CV administration (97 +/- 17 s vs. 70 +/- 12 s, respectively; p = 0.17) with total dose delivered of sternal being 86% of the dose delivered via CV (p = 0.22).Conclusions: IO drug administrations via either the sternum or tibia were effective during CPR in anesthetized swine. However, IO drug administration via the sternum was significantly faster and delivered a larger dose. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Intraosseous; Cardiopulmonary resuscitation; CPR; Pharmacokinetics; Tracers; Drug delivery